PELATIHAN PEMANFAATAN ASAP CAIR UNTUK PENGAWET IKAN ASAR BAGI SEKELOMPOK IBU-IBU DI KOTA JAYAPURA - Ilham Salim; Supeno Supeno; Yohanes B.J. Rusmanta; Himawan Himawan (JURNAL PENGABDIAN PAPUA, 2023)
Some community groups in Jayapura City smoke fish using iron wood, matoa wood, or coconut shells and from the roasting results it can be seen that the physical color can vary in the fish. The aim of the activity is to conduct training for a group of people with the aim of helping community groups to be able to participate in applying fish preservation from natural ingredients, namely by using liquid smoke. The training was held in July 2022 in Buton Village, Yabansai Village, Heram District, Jayapura City with lecture and practice methods. The evaluation was carried out to find out whether the participants were skilled in using liquid smoke in processing asar fish using liquid smoke. clean. The results of the activity showed that the participants were very enthusiastic and understood the training material on preserving fish from natural ingredientsKeywords: asap cair; ikan asar; Jayapura; wood